2013
DOI: 10.1371/journal.pone.0073320
|View full text |Cite
|
Sign up to set email alerts
|

Severe Septic Patients with Mitochondrial DNA Haplogroup JT Show Higher Survival Rates: A Prospective, Multicenter, Observational Study

Abstract: ObjectiveIn a previous cohort study (n=96), we found an association between mitochondrial (mt) DNA haplogroup JT and increased survival of severe septic patients, after controlling for age and serum lactic acid levels. The aim of this research was to increase the predictive accuracy and to control for more confounder variables in a larger cohort (n=196) of severe septic patients, to confirm whether mtDNA haplogroup JT influences short and medium-term survival in these patients.MethodsWe conducted a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The results of our study (to our knowledge, the largest series providing data on mtDNA and survival in septic patients comprising 96 patients of the first series and 196 patients of the second series with a total of 292 patients) confirmed that haplogroup JT septic patients had increased 30-day and 6-month survival by comparison with non-JT haplogroup patients (93). In the multiple logistic regression analysis, we found that mtDNA haplogroup JT was associated with higher survival at 30-days (OR, 0.38; 95% CI, 0.15 to 0.95; P = 0.04) and 6 months (OR, 0.40; 95% CI, 0.17 to 0.90; P = 0.03) after controlling for age, sex, serum IL-6 levels, and the SOFA score.…”
Section: Determination Of Mitochondrial Deoxyribonucleic Acid Haplogroupsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of our study (to our knowledge, the largest series providing data on mtDNA and survival in septic patients comprising 96 patients of the first series and 196 patients of the second series with a total of 292 patients) confirmed that haplogroup JT septic patients had increased 30-day and 6-month survival by comparison with non-JT haplogroup patients (93). In the multiple logistic regression analysis, we found that mtDNA haplogroup JT was associated with higher survival at 30-days (OR, 0.38; 95% CI, 0.15 to 0.95; P = 0.04) and 6 months (OR, 0.40; 95% CI, 0.17 to 0.90; P = 0.03) after controlling for age, sex, serum IL-6 levels, and the SOFA score.…”
Section: Determination Of Mitochondrial Deoxyribonucleic Acid Haplogroupsupporting
confidence: 71%
“…In addition, mtDNA can influence the survival of septic patients, possibly due to the impact of mtDNA on mitochondrial function. The influence of mtDNA on the survival of septic patients has been scarcely studied (90)(91)(92)(93).…”
Section: Determination Of Mitochondrial Deoxyribonucleic Acid Haplogroupmentioning
confidence: 99%
“…A previous study identified increased survival in haplogroup JT septic patients and showed that survival may be due to an SNP defining haplogroup JT and not haplogroup J-or Tdefining variants. 17 Another study 18 compared European haplogroup J and H mtDNA using cytoplasmic hybrids or "cybrids" (experimental hybrid cells containing mtDNA from different sources placed in a uniform nuclear DNA background), and haplogroup J cybrids exhibited increased mitochondrial transcription levels and a greater than 2-fold increase in mtDNA copy number compared with haplogroup H cybrids. This is one of the few examples demonstrating functional consequences for variants underlying specific haplogroups.…”
mentioning
confidence: 99%
“…Several population studies have also evaluated associations between health outcomes and mitochondrial haplogroups. Haplogroup JT has been associated with diverse phenotypes, including improved outcomes following a diagnosis of sepsis (Lorente et al, 2013(Lorente et al, , 2016, reduced risk of diminished ovarian reserve (May-Panloup et al, 2014), and reduced risk of Parkinson disease (Hudson , 2013). In one study of octo/nonagenarians, individuals with haplogroup J had lower systolic blood pressure and glutathione peroxidase activity (Rea et al, 2013).…”
Section: Discussionmentioning
confidence: 99%